Exploring Humla’s awe-inspiring butterfly diversity, confirming the presence of Agriades dis Grum-Grshimailo, 1891 in Nepal - Suwal, Sanej Prasad; Hengaju, Krishna Dev; Kusi, Naresh (Nepalese Journal of Zoology, 2025)
This study provides a checklist of butterfly species from Humla District, Karnali Province, Nepal, based on field observations conducted in July 2017 and secondary data. A total of 39 butterfly species were documented, of them 31 were recorded during this study. The majority of species belong to the Nymphalidae family (19 species), followed by Lycaenidae (10 species), Pieridae (6 species), Papilionidae (2 species), Riodinidae (1 species), and Hesperiidae (1 species). This checklist includes revised information on altitudinal, seasonal, and geographical distributions, alongside detailed descriptions of notable and rarely observed species such as Agriades dis, Callerebia nirmala, and Colias ladakensis. The findings reveal the rich biodiversity of butterflies in this remote Himalayan region, with several species extending their known ranges and appearing at new altitudinal zones. Highlighting the conservation significance, these results underscore the importance of ongoing biodiversity assessments in the face of environmental and climate changes. This research contributes valuable baseline data for Nepal’s butterfly fauna, informing future conservation strategies and ecological studies in the Himalayan ecosystem.